Enhancing Early Childhood Memory in Hadith Memorization Through Movement-Based Training - Deri Gusmita; Nuril Huda (Journal of Comunity Service in Early Childhood Education, 2025)
Background: Early childhood represents a critical period for cognitive and memory development, including the ability to memorize and understand religious teachings such as hadith. However, field observations indicate that many children experience difficulties in memorizing hadith sequentially and recalling previously learned material. This condition highlights the need for innovative and developmentally appropriate learning approaches. Aims: This community service program aims to enhance early childhood memory in hadith memorization through a movement-based training approach. Methods: This program employed a training-based community service approach integrated with mentoring and evaluation. The implementation was conducted over one month, from October 29 to November 29, 2023, involving children aged 5–6 years and classroom teachers. The program consisted of preparation, implementation, and evaluation stages. Activities included movement-based memorization training, guided practice sessions, and teacher mentoring. Data were collected through observation and documentation using predefined indicators and analyzed descriptively. Results: The results indicate a significant improvement in children’s memory and learning outcomes. Memory skills increased from 40% to 85%, while understanding and application of hadith improved from 35% to 80%. Children’s participation and cooperation increased from 50% to 90%, and positive behavioral changes improved from 45% to 85%. Teacher engagement also increased from 60% to 95%, indicating the effectiveness of the training approach. Conclusion: Movement-based training is effective in enhancing early childhood memory in hadith memorization. The integration of movement, practice, and mentoring creates engaging and meaningful learning experiences that support cognitive and behavioral development. This approach can be adapted as an alternative method in early childhood religious education.